Survey of Hawksbill Turtle (Eretmochelys imbricate) Health Condition in Terms of Parasites and Microbes in Alas Purwo National Park, Indonesia - Qurrota A'yunin; Happy Nursyam; Sri Andayani; Maftuch Maftuch; Lukluk Intan Maftuchah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2017)
Indonesian waters have six types of turtles that can live, spawn and breed. Sea turtle conservation becomes an important and urgent program to be done in order to protect and save sea turtle population in Indonesia. One of the factors that most affect the turtle population is the cause of degradation of pathogenic factors. Alas Purwo National Park, East Java, there is some communities that have activities turtle conservation. Conservation is done by securing and protecting turtle eggs. Turtle eggs that have hatched are released into the sea once it is ready. This study aims was to determine the type of bacteria and fungi that infect hatchlings and environmental factors that influence. This research is descriptive method to Hawksbill turtle (Eretmochelys imbricate) is by way of random sampling. Sampling of microbes in sea turtle was conducted using cotton swab method and then microbes was cultured and indentified in laboratory. The results showed The kind of parasites and microbes which were indentified in hatching and adult Hawksbill sea turtles were fungus with genus Aspergillus sp., Geotrichum sp., Fusarium sp., and Gliocladium sp. ; bacteria are Pseudomonas aeruginosa and Enterobacter cloaceae; and parasite is Chelonibia testudinaria barnacles. The parameter average value of water in pond indicated 28.1 – 29.2°C for temperature, 32 - 34 ‰ for salinity, 7.78 – 8.2 for pH, and 3.86 – 4.21 mg/L for DO.